Selection of Non-Thermal Technology for Honey Pasteurization Machine Using Multi-Criteria Decision Making - Muhammad Dani Setiawan; Lobes Herdiman; Taufiq Rochman (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2022)
Abstract. Honey is a natural food product from a sweet viscous substance formed from flower nectar by honey bees. Honey processing using the pasteurization method has limitations, one of which is temperature. As a result, fungi and spores present in honey have not been eliminated. Non-thermal technology (NTT) is a solution to this limitation, because NTT is a process that applies little or no heat, with the aim of food receiving microbial inactivation, and can extend life, maintain physical quality, nutrition, and sensory freshness. NTT is commonly used in industry, namely in High-Pressure Processing (HPP), Pulsed Electric Field (PEF), Pulsed Light, Cold Plasma (CL), and Ultra Sound (US). Adjustment to the characteristics of honey is the reason for choosing non-thermal technology. The selection was carried out using the MCDM method, which integrates AHP-TOPSIS. The result is PEF being the selected NTT with a relative closeness of 0.773.